2020
DOI: 10.1037/xge0000973
|View full text |Cite
|
Sign up to set email alerts
|

On repression, and avoiding red herrings.

Abstract: In this response to Otgaar et al. (in press) we point out that their concern with the notion of unconscious repression is a classic example of a red herring, as it has never been endorsed as an explanation of recovered memories. We also note that Otgaar et al. have misunderstood the purpose of our article (Brewin, Li, Ntarantana, Unsworth, & McNeilis, 2019). Its aim was to demonstrate that many of the claims made by psychologists about the public's views on memory do not rest on sound methodology. Beliefs abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…To recap, scholars have sometimes argued that research on the belief in repressed memory is limited as it has exclusively focused on a narrow set of statements (Brewin et al, 2020). In the current studies, we have shown that high agreement ratings exist when a wide variety of statements are used assessing various aspects of repressed memory and dissociative amnesia.…”
Section: Limitations and Future Researchsupporting
confidence: 50%
See 1 more Smart Citation
“…To recap, scholars have sometimes argued that research on the belief in repressed memory is limited as it has exclusively focused on a narrow set of statements (Brewin et al, 2020). In the current studies, we have shown that high agreement ratings exist when a wide variety of statements are used assessing various aspects of repressed memory and dissociative amnesia.…”
Section: Limitations and Future Researchsupporting
confidence: 50%
“…For one, in Sauerland and Otgaar's (2022) study, there were only 2 statements related to repressed memory that were surveyed at the start and end of the course (i.e., "The mind is capable of unconsciously "blocking out" memories of traumatic events," "A poor memory for childhood events is indicative of a traumatic childhood"). Scholars have criticized past survey work on repressed memory because oftentimes only a small set of belief statements was used to examine repressed memory (Brewin et al, 2020). This is problematic because repressed memory is a complex concept which is difficult to capture in merely one or two statements.…”
Section: Changing Beliefs In Repressed Memorymentioning
confidence: 99%
“…However, an alternative variant of repression presumably happens through conscious control and is sometimes referred to as memory suppression or motivated forgetting (e.g., Anderson & Green, 2001). Brewin, Li, et al (2020) argued that memory suppression serves as a likely candidate for the forgetting of autobiographical memories and their recovery after many years. Nevertheless, no research has convincingly demonstrated memory suppression for autobiographical experiences in the laboratory (Otgaar et al, 2019), let alone for years or decades in everyday life.…”
Section: Memory Suppression and False Memoriesmentioning
confidence: 99%
“…First, in most of these studies, participants only received one item concerning repressed memory. However, repressed memory is a complex phenomenon which cannot be simply captured by one item (Brewin et al, 2020). Therefore, in the past years, researchers started to provide participants several items tapping into different dimensions and variations of repressed memory to gauge their beliefs.…”
Section: Believing In Repressed Memorymentioning
confidence: 99%